2014
DOI: 10.1007/s00404-014-3572-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma serotonin levels are elevated in pregnant women with hyperemesis gravidarum

Abstract: Our findings support the possible role of serotonin in the pathogenesis of hyperemesis gravidarum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
10
0
1
Order By: Relevance
“…Our data on the pregnancy-increased cerebellar content of tryptophan are in line with the activation of serotonergic signaling observed during pregnancy, because tryptophan is the serotonin precursor [36]. The interaction between the levels of serotonin and estrogens also underlies sex-dimorphic prevalence of the serotonin-linked diseases, including migraine, depression, eating disorders and pregnancy-associated pathologies [36,37].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our data on the pregnancy-increased cerebellar content of tryptophan are in line with the activation of serotonergic signaling observed during pregnancy, because tryptophan is the serotonin precursor [36]. The interaction between the levels of serotonin and estrogens also underlies sex-dimorphic prevalence of the serotonin-linked diseases, including migraine, depression, eating disorders and pregnancy-associated pathologies [36,37].…”
Section: Discussionsupporting
confidence: 84%
“…Because these amino acids are highly correlated independent of pregnancy and/or hypoxia (Table 3), metabolism of cerebellar lysine appears to be a more likely contributor to specific adaptations imposed by pregnancy. This is further supported by the fact that lysine is known as an antagonist of a serotonin receptor [60], with serotonergic signaling increased in pregnancy [36,37] and depressed upon increased synthesis of homoarginine from lysine [61].…”
Section: Discussionmentioning
confidence: 91%
“…Hyperemesis gravidarum is a severe form of nausea and vomiting in pregnant women, and elevated serotonin level is found associated with hyperemesis gravidarum and PONV as well. 18 In our study, WBC, HGB, N and L counts, N/L ratio, RBC, MCV, MCH, MCHC and RDW had similar values for both the POV and control groups. According to our results, these parameters provide predictable information for POV.…”
Section: Discussionsupporting
confidence: 69%
“…An analysis of insurance data of 11,016 women who gave birth found that a pre-pregnancy psychiatric diagnosis doubled the risk of developing HG and pre-pregnancy psychiatric and somatic conditions quadrupled the risk, which suggest that these disorders, or a common etiologic factor, may play a role in the development of HG in some women (Seng et al 2007). Women with HG have been found to have significantly higher levels of plasma serotonin compared to women with N/V of pregnancy and pregnant controls (Cengiz et al 2015).…”
Section: Pathogenesismentioning
confidence: 97%